Nathanlambson wrote:

(x−y)(y−x+1) = ?

(1) x−y=2

(2) y−x+1=−1

\(? = \left( {x - y} \right)\left( {y - x + 1} \right)\)

\(\left( 1 \right)\,\,\,\boxed{x - y = 2}\,\,\,\, \Rightarrow \,\,\,y - x = - 2\,\,\,\, \Rightarrow \,\,\,\boxed{y - x + 1 = - 2 + 1}\)

\(? = 2 \cdot \left( { - 2 + 1} \right)\,\,\,\,\,{\text{SUF}}.\)

\(\left( 2 \right)\,\,\boxed{y - x + 1 = - 1}\,\,\, \Rightarrow \,\,\,y - x = - 2\,\,\,\, \Rightarrow \boxed{x - y = 2}\,\,\)

\(? = 2 \cdot \left( { - 1} \right)\,\,\,\,{\text{SUF}}.\)

The above follows the notations and rationale taught in the GMATH method.

Regards,

fskilnik.

_________________

Fabio Skilnik :: http://www.GMATH.net (Math for the GMAT)

Course release PROMO : finish our test drive till 30/Sep with (at least) 60 correct answers out of 92 (12-questions Mock included) to gain a 70% discount!